Preliminary study on formulation of pva-based face mask incorporated with sugarcane bagasse microfibrillated cellulose - Jimat, Dzun Noraini; Mohamad, Istisyhad; Amid, Azura; Azmi, Azlin Suhaida; Abd Wahab, Mohd Firdaus (IIUM Journal Publication Unit, 2020)
Cellulose facial masks have gained a huge interest in the cosmetic industry. Cellulose can be extracted from plant biomass, bacteria and algae. In this study, several formulated PVA-based facial masks (F1, F2, F3, F4) incorporated with microfibrillated cellulose extracted from sugarcane bagasse (MFC-SCB) were prepared. The concentration of polyvinyl alcohol (PVA) was varied (5%–20% (w/w)) while the concentration of microfibrillated cellulose of sugarcane bagasse (MFC-SCB) was fixed at 5% (w/w) to get the appropriate composition of the facial masks. The MFC-SCB was extracted through chemical treatment assisted with ultrasonication. Sensory tests in terms of adhesion to the skin, spreadability, color, odor, and drying time were performed. These tests were carried out by requesting the volunteers to rate the performance of the masks. The results showed that the formulated facial mask F3 (15% [w/w] of PVA and 5% [w/w] of MFC-SCB) has the highest average score (13.9) which is 82% from the total score compared to other formulated masks. However, the standard formulation mask F5 (15% [w/w] of PVA and 5% [w/w] of sodium carboxylmethyl cellulose, CMC) achieved the highest score (13.5) compared to F3 (12.5). The findings of this study proved that the presence of MFC-SCB with PVA has a competitive performance with the standard facial mask formulation.